Comparative assessment of valuable agronomic traits of the Chinese collection of common buckwheat samples in the conditions of the Akmola region - Nuriya Sarbassova; Margarita Abylkairova; Nurgul Kulikova; Aliya Kekenova; Raykhan Utegenova; Issmayl Ketebaev; Karina Batyrbaeva; Arukhan Sarbassova; Yeldos Kulzhabaev (European Research Materials, 2026)
Buckwheat is a leading cereal crop, possessing high nutritional and dietary value. The grain is used to produce cereals and flour and is rich in easily digestible proteins, B vitamins, trace elements, and rutin, which is beneficial for strengthening blood vessels. Due to its gluten- free nature, buckwheat is valued in medicinal and baby food [1]. Vegetative mass and by-products of grain processing are used in animal husbandry as nutritious feed [2]. Buckwheat plays an important agronomic role. By releasing organic acids, its root system helps convert poorly soluble phosphorus compounds into a more readily available form, improving soil fertility and making buckwheat a good precursor for many crops [3]. The primary center of buckwheat domestication is considered to be the interior regions of Southeast Asia (western China, Tibet, eastern India), where cultivation of its wild ancestors began around the sixth millennium BC. From this region, the crop spread to Central Asia, and subsequently to the Middle East and Europe. Archaeological and paleontological evidence indicates a wide geographic distribution of early cultivation: the oldest traces in Finland date back to 5300 BC, pollen samples in Japan to 4000 BC, and finds in China to 2600 BC. Possessing unique biological plasticity, buckwheat is recognized as the highest-altitude domesticated crop in the world, as evidenced by its successful cultivation on the Tibetan Plateau (Yunnan Province). Large-scale cultivation of the crop continued in Siberia, India, Turkey, and Japan. Buckwheat only entered European agricultural circulation on a large scale in the 15th century, reaching Italy and neighboring countries via the trade routes of the Black Sea basin. During the colonial era, Europeans brought the crop to North America.